2004
DOI: 10.1111/j.1365-3164.2004.00410_2-6.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and activity of prednisone and prednisolone in the feline patient

Abstract: In veterinary dermatology, the therapeutic approach to numerous diseases (e.g. hypersensitivity and autoimmunity) centres upon suppression of an overactive immune system. By contrast, in other situations such as infectious diseases and cancer, it may be desirable to enhance an ineffective immune response. Currently available methods of such immunomodulation are relatively crude. Immunosuppression is generally achieved with systemic administration of glucocorticoids, with or without concurrent cytotoxic agents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 0 publications
4
31
0
2
Order By: Relevance
“…While higher systemic exposure of prednisolone was previously reported in cats [13], the rate of drug absorption and elimination was comparable to our present results. A feasible explanation for the different results could be attributed to differences in animal weight and, thus, in volume of distribution.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While higher systemic exposure of prednisolone was previously reported in cats [13], the rate of drug absorption and elimination was comparable to our present results. A feasible explanation for the different results could be attributed to differences in animal weight and, thus, in volume of distribution.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we reported plasma half-life time of elimination of 0.66 h, comparable to previous reports in cats [13]. On the contrary, longer T 1/2el values (around 3 h) were reported after oral prednisolone in humans [6, 29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is not clear if the differences are due to decreased gastrointestinal absorption or to decreased hepatic conversion of prednisone to prednisolone (Graham-Mize and Rosser, 2004). However, this belief does not seem to be correct.…”
Section: Oralmentioning
confidence: 99%
“…The majority of these cats received long-term systemic glucocorticoids. Some cats cannot convert the prodrug prednisone to the active drug prednisolone 11) , so prednisolone is the preferred form in cats 26) . In our study, only 56.3% of the cats responded to prednisone, while 83.7% responded to prednisolone.…”
Section: Discussionmentioning
confidence: 99%